Avobenzone-loaded and omega-3-enriched lipid formulations for production of UV blocking sunscreen gels and textiles - Caldas, Ana Rita (2021)
Given the growing harmful effects of ultraviolet (UV) radiation there is an urgent need to develop effective strategies to prevent skin damages. Therefore, hydrogel or cotton and wool fabrics were impregnated with avobenzone (AVO)-loaded and omega-3 (ω3)-enriched lipid formulations (liposomes – LIP, nanostructured lipid carriers – NLC and solid lipid nanoparticles – SLN) to obtain UV blocking sunscreen gel or functional textiles. To evaluate the physicochemical characteristics of AVO and the sun blocking performance of the formulations incorporated in hydrogels or textiles, in silico and in vitro studies were conducted. In silico studies indicated that AVO can permeate the epithelium, and lipid formulations could be a promising strategy for incorporating and retaining AVO. Furthermore, all lipid formulations showed an entrapment efficiency of AVO of ca. 100 % and a loading capacity between 7 and 12 %. The presence of AVO was confirmed by ATR-FTIR and SEM analysis. In vitro release profiles showed that the UV filter was almost totally retained within the lipid formulations (release of only 4.2 ± 2.5 % at 6 h) with similar results obtained for textiles. After assessing the cytotoxicity, cationic formulations loaded with AVO showed to be cytotoxic in a human keratinocyte cell line (NCTC 2544 cells) as opposed to AVO-loaded anionic formulations after 24 h. Photodegradation studies demonstrated that lipid formulations have photoprotective properties by stabilizing AVO but the photoprotective role could not be attributed to ω3 despite its antioxidant effect evaluated by ATR-FTIR. Overall, it is possible to conclude that SLN and NLC were more effective as UV protectors than LIP, and that each formulation can have different applications. Negatively charged NLC and SLN can be used for UV protection in contact with the skin either in sunscreen gel or clothing, while positively charged NLC and SLN should be reserved as UV protectors of tissues not in contact with skin (e.g., umbrellas, curtains, etc.).